Dissolution mechanism of Al2O3 in refining slags containing Ce2O3 - Wang, Lijun; Wang, Qi; Li, Jian Min; Chou, Kuo-chih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In the present work, the rate of dissolution of dense Al2O3 rods in CaO-SiO2-Al2O3 and CaO-SiO2-Al2O3-Ce2O3 slags were carried out in the temperature range 1793K (1520oC) - 1853K (1580oC) under static conditions. The cross section of the rod and the boundary layers were identified and analyzed by SEM-EDS. The dissolution of Al2O3 was favored with increasing CaO/Al2O3 ratio as well as temperature and with the addition of Ce2O3. An intermediate product, 3CaO·5Al2O3·Ce2O3 was detected. The mechanism of dissolution of Al2O3 in the Ce2O3-containing slag is discussed. Based on the experimental results, the Al2O3 dissolution is considered to consist of three steps, viz. 1) the formation of calcium aluminates CaO·Al2O3 at the interface 2) the formation of 3CaO·5Al2O3·Ce2O3 as the reaction progresses; and 3) the dissolution of 3CaO.5Al2O3.Ce2O3 into the slag.